Different forms of government regimes and covid-19 outcomes in Africa - Masiya, Ulemu Vanessa (University of the Witwatersrand, Johannesburg, 2024)
This study examines extent to which the government regime types contributed to explaining the low COVID 19 mortality and infection cases in Africa. The study analyses panel data from 54 countries in Africa across a 2-year period from January 2020 to December 2021. The following factors of demography, GDP per Capital, health expenditure, and government effectiveness were included as control variables in the models. The results of the panel regression analysis indicated that while authoritarian and partially democratic regimes were positively associated with a surge in COVID-19 cases and fatalities compared to fully democratic countries in Africa, the association lacked statistical significance. In contrast, government effectiveness and health expenditure were observed to be negatively associated with reduced COVID 19 mortality and infection rates at the 5 percent significance level. Hence, this result emphasized the role of good governance and increased health spending in managing the pandemic’s mortality and infection rates across the different types of government regimes in Africa.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management (in the field of Governance and Management) to the Faculty of Commerce, Law, and Management, School of Governancel, University of the Witwatersrand, Johannesburg, 2024
Keywords: Regime types; COVID-19 infection rates; Authoritarian regimes; partly democratic regimes; public health expenditure; Government effectiveness; Urbanization; Population age distribution; Democracy index; COVID-19 fatalities; GDP per Capital; Africa; SDG-3: Good health and well-being